A PRODUÇÃO DE EMBUTIDOS COMO ALTERNATIVA DE RENDA PARA UNIDADES DE PRODUÇÃO AGRÍCOLAS FAMILIARES - Mackoski, Fernando d. S.; Uhde, Leonir; Berto, Jorge L.; Fernandes, Sandra B. V.; Garcia, Dagmar C.; Quadros, Valmir J. d. (Salão do Conhecimento, 2013)
Resumo